2017
DOI: 10.18632/oncotarget.17350
|View full text |Cite
|
Sign up to set email alerts
|

Patients with chronic lymphocytic leukemia and complex karyotype show an adverse outcome even in absence of TP53/ATM FISH deletions

Abstract: Genomic complexity identified by chromosome banding analysis (CBA) predicts a worse clinical outcome in CLL patients treated either with standard or new treatments. Herein, we analyzed the clinical impact of complex karyotypes (CK) with or without high-risk FISH deletions (ATM and/or TP53, HR-FISH) in a cohort of 1045 untreated MBL/CLL patients. In all, 99/1045 (9.5%) patients displayed a CK. Despite ATM and TP53 deletions were more common in CK (25% vs 7%; P < 0.001; 40% vs 5%; P < 0.001, respectively), only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 25 publications
3
34
0
Order By: Relevance
“…7 However, CK remained a heterogeneous group. 5 In our series, we could define 4 CK groups according to their FISH status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 However, CK remained a heterogeneous group. 5 In our series, we could define 4 CK groups according to their FISH status.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately one third of CK displayed TP53 loss, one third ATM 9 Other data showed that CK cases had a comparable OS as pts exhibiting TP53 loss (whatever CBA result), and pts cumulating CK and TP53 loss had the lower overall survival. 5 Here we could define two supplementary subgroups of CK pts, CK without HR-FISH and CK with ATM loss, which represented 67% of CK cases remained to be clinically investigated.…”
Section: Discussionmentioning
confidence: 99%
“… More than 20 metaphases were analyzed. Complex karyotype (CK) was defined as ≥3 chromosome aberrations detected in at least two metaphases …”
Section: Methodsmentioning
confidence: 99%
“…Similar studies have also shown that the presence of a complex karyotype is associated with a worse prognosis (Jaglowski et al , ; Travella et al , ) and poorer treatment response rates, even in the current era of novel therapies (Thompson et al , ). More recently, a complex karyotype was shown to be associated with poor outcome in the absence of mutations of TP53 or ATM (Puiggros et al , ) and was an independent prognostic marker in a prospective study of patients receiving chlorambucil based chemo‐immunotherapy (Herling et al , ). Furthermore, Baliakas et al () have demonstrated that a threshold for defining complex karyotype of 5 or more chromosomal lesions is associated with mutations of TP53 and, perhaps due to this association, an aggressive clinical course.…”
Section: Cytogeneticsmentioning
confidence: 99%